Elemen Visual dan Respon Pengunjung Terhadap Interior Noch Kafe di Kota Malang - Achmad Ari Fathoni; Swastika Dhesti Anggriani; Lilik Indrawati (Universitas Gadjah Mada, 2022)
Ngopi culture of the Indonesian people today will proliferate services that provide various types of coffee drinks and comfortable and aesthetically pleasing seats. One of the cafes that provide this service is Noch Kafe, located in Malang City. This study aims to determine the visual elements of the interior at Noch Kafe and to determine the visitor's response to the visual elements of the interior. The study was conducted using qualitative methods to analyze descriptive data and images, and quantitative methods of percentages to analyze visitor response data. Descriptive data were obtained through interviews, documentation, and observation, while the response data were obtained through questionnaires. The results showed that the visual elements of the interior have a Scandinavian style with a blend of modern styles and are adapted to the climatic conditions and Indonesian culture. Space-forming elements are made simple and function properly. These can be seen through application of wood materials and the choice of white color on the walls. In addition, the form adapts to climatic conditions, as seen in glass ceilings and walls. Furniture is also made of wood and is simple in shape and according to its function. The results of visitors' responses to visual elements influenced by personal experience show a good/excellent response to most of the visual elements. However, the survey results also concludes that visitors are disfavored with the shape of the table, the shape of the shelves, the night lighting on the terrace area, and the photo/picture decoration.